2014
DOI: 10.1614/wt-d-14-00029.1
|View full text |Cite
|
Sign up to set email alerts
|

Palmer Amaranth (Amaranthus palmeri) Management in GlyTol®LibertyLink®Cotton

Abstract: Field trials were conducted in Lubbock, TX in 2010 and 2011 to evaluate tank-mix combinations of glyphosate and glufosinate in GlyTol®LibertyLink®cotton for control of Palmer amaranth. Herbicide treatments included glyphosate and glufosinate applied at various tank-mix rate combinations (1X:1X, 1X:0.75X, 1X:0.5X, 1X:0.25X and 1X:0X of glyphosate plus glufosinate), proportional tank-mix rate combinations (1X:0X, 0.75X:0.25X, 0.5X:0.5X, 0.25X:0.75X, and 0X:1X of glyphosate plus glufosinate, where X is 0.84 kg ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…), and velvetleaf (Abutilon theophrasti Medik.) (Bethke et al 2013;Reed et al 2014). Combinations of glyphosate mixtures with fomesafen or sulfentrazone were antagonistic on a number of broadleaved weeds, a result that is attributable to the rapid activity of the latter herbicides minimizing glyphosate transport (Starke and Oliver 1998;Wehtje et al 2008).…”
mentioning
confidence: 99%
“…), and velvetleaf (Abutilon theophrasti Medik.) (Bethke et al 2013;Reed et al 2014). Combinations of glyphosate mixtures with fomesafen or sulfentrazone were antagonistic on a number of broadleaved weeds, a result that is attributable to the rapid activity of the latter herbicides minimizing glyphosate transport (Starke and Oliver 1998;Wehtje et al 2008).…”
mentioning
confidence: 99%
“…Amaranthus palmeri and A. tuberculatus are two major weed species infesting cotton-(Gossypium hirsutum L.) production fields in Texas [7][8][9]. These two species are highly competitive with cotton and can cause significant yield losses.…”
Section: Introductionmentioning
confidence: 99%
“…Glufosinate fb dicamba was not as effective as dicamba fb glufosinate 7 and 14 DASA in 2018 and 7 and 21 DASA in 2019. Reed [11] reported minimal control of Palmer amaranth of similar size with two or three sequential applications of glufosinate. In contrast, Corbett et al [17] reported 100% control of 2 to 5 cm and 8 to 10 cm Palmer amaranth following sequential applications of glufosinate made 10 days apart at lower rates of glufosinate per hectare.…”
Section: < 10 CM Palmer Amaranthmentioning
confidence: 99%
“…Reed [11] reported applications of glufosinate alone controlled 5 to 10 cm Palmer amaranth greater than 15 to 20 cm Palmer amaranth 14 and 21 days after treatment. Whitaker et al [19] reported that although a second application of glufosinate initially improved Palmer amaranth control, many weeds survived and grew to heights too large to be controlled by a layby application when Palmer amaranth size at initial application was 5 to 8 cm.…”
Section: > 30 CM Palmer Amaranthmentioning
confidence: 99%
See 1 more Smart Citation